2020
DOI: 10.3389/fphys.2020.01020
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E Induces Autophagy-Involved Apoptosis in Intestinal Epithelial Cells

Abstract: Apoptosis plays a crucial role in maintaining the structural and functional integrity of the intestinal epithelial barrier. Autophagy mediates injury to and repair of the intestinal epithelial barrier through multiple pathways in pathophysiological conditions. Our earlier study has found that cucurbitacin E (CuE) regulates the proliferation, migration, and permeability of human intestinal epithelial cells (IECs); however, its effects and mechanisms on apoptosis and autophagy are still unclear. This study repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Chemotherapeutic agents play a role as oxidants and regulate the mitochondrial apoptotic pathway by inducing ROS‐mediated activation of Fas ligand and TRAIL (Altinoz et al, 2022; Kim et al, 2008; Wang et al, 2008). Previous studies have reported that cucurbitacins exhibit anticancer effects by modulating apoptotic and autophagic signaling mechanisms through ROS induction (Kim et al, 2020; Luo et al, 2018; Ma et al, 2016; Song et al, 2020; Zhang & Li, Park, et al, 2012). CuD activates the ROS/p38 pathway and induces apoptosis in pancreatic cancer cells (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotherapeutic agents play a role as oxidants and regulate the mitochondrial apoptotic pathway by inducing ROS‐mediated activation of Fas ligand and TRAIL (Altinoz et al, 2022; Kim et al, 2008; Wang et al, 2008). Previous studies have reported that cucurbitacins exhibit anticancer effects by modulating apoptotic and autophagic signaling mechanisms through ROS induction (Kim et al, 2020; Luo et al, 2018; Ma et al, 2016; Song et al, 2020; Zhang & Li, Park, et al, 2012). CuD activates the ROS/p38 pathway and induces apoptosis in pancreatic cancer cells (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cucurbitacins are natural compounds known for their antiproliferative activity in many types of cancer cells, lacking specific cell and tissue specificity (Chung et al, 2015). Studies have shown that cucurbitacins exert their anticancer properties by targeting multiple signaling pathways, including JAK/STAT3 (Üremiş et al, 2022b), Wnt/β‐catenin (Yang et al, 2020), MAPK (Üremiş et al, 2022b), PI3K/AKT/mTOR (Üremiş et al, 2022b), Ras/Raf/MEK/ERK (Chan et al, 2010), and autophagy (Song et al, 2020), rather than a single overactivated pathway in cancer. Furthermore, cucurbitacins exhibit potent cytotoxic effects at low concentrations, allowing for the reduction of therapeutic doses compared to conventional chemotherapeutic drugs used at high concentrations (Jing et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inducing apoptotic cell death, recent studies have demonstrated that Cu E can also promote autophagy by modulating key signaling pathways, such as the PI3K/Akt pathway and the mTOR signaling pathway [31,38]. To further investigate the effects of Cu E on autophagy in A549 cells, we examined the levels of regulatory proteins by Western blotting.…”
Section: The Effects Of Cu E On Autophagy In A549 Cellsmentioning
confidence: 99%
“…Several studies have investigated the effects of Cu E on autophagy, although its impact on cell death remains controversial. Some findings suggest that Cu E inhibits the PI3K/AKT/mTOR signaling pathway, leading to the activation of autophagy in human cancer cells and intestinal epithelial cells [31,38]. Conversely, Cu E has been found to induce protective autophagy mediated by ROS in lung 95D cells [39].…”
Section: Introductionmentioning
confidence: 99%